Оценка погрешности асимптотического представления угловых колебаний оси симметрии вращающегося твердого тела - Коносевич, Б.И. (Прикладная механика, 2014)
Отримано оцінку похибки розв’язку Вентцель – Крамерса – Бріллюена рівнянь кутового руху осі симетрії обертання твердого тіла (снаряда). Встановлено, що порядок цієї оцінки не залежить від згасання низькочастотних коливань осі симетрії снаряда. An estimate of error of the Wentzel – Kramers – Brillouin’s solution for equations of angular motion of the axis of symmetry of a projectile is obtained. It is established that order of this estimate does not depend on the damping of low-frequency angular vibrations of the axis of symmetry.